Development and validation of the clinical judgment capability questionnaire in nurses: A sequential exploratory mixed method study - Ali Dehghani (Elsevier, 2024)
Background: Clinical judgment is one of the most important competencies required for safe care, decision-making, and diagnosis in nursing profession. Therefore, it is necessary to examine clinical judgment in nursing care. Existing a standard questionnaire based on cultural and social conditions can accurately evaluate clinical judgment in nurses. Objective: The present study aimed to develop and validate clinical judgment capability questionnaire in nurses. Design: The current research was a sequential exploratory mixed method study. Setting: The teaching hospitals affiliated to Jahrom University of Medical Sciences in the South of Iran in 2023. Participants: Twelve clinical nurses were included in the qualitative part and 181 nurses in the quantitative part. Methods: The study was conducted in two parts: one qualitative and one quantitative. In the qualitative part, the concept of clinical judgment was explored using qualitative content analysis. Then, the initial pool of items was generated to develop a questionnaire. In the quantitative part, psychometric properties of the questionnaire were evaluated including face, content, and structure validity and reliability (internal consistency and stability). Results: After examining the psychometric properties, 22 items were developed for the final questionnaire. The results of factor analysis led to the extraction of four factors, including noticing, interpreting, responding, and reflecting. The internal consistency of the questionnaire was confirmed with a Cronbach's alpha coefficient of 0.95 and its stability with an intraclass correlation coefficient of 0.84. Conclusion: The developed 22-item questionnaire is a valid and reliable tool for assessment of clinical judgment capability in nurses.